Two new species of Aulacaspis Cockerell, 1893 (Hemiptera: Coccomorpha: Diaspididae) from China - Tian, Feng; Xing, Jichun (Zootaxa, 2022)
Two new armoured scale insects in the genus Aulacaspis (Hemiptera: Coccomorpha: Diaspididae) are described and illustrated from Guizhou Province, China. Aulacaspis paralonganae sp. n. was collected from the host-plant Schima superba (Theaceae) and A. guiyangensis sp. n. was collected from Cinnamomum camphora (Lauraceae). Aulacaspis longanae Chen, Wu & Su 1980 is redescribed and a new host-plant record is reported. The type specimens of the two new species and material of A. longanae are deposited in the Institute of Entomology, Guizhou University, Guiyang, China. An identification key based on adult females is provided to separate Chinese species of Aulacaspis.